Palladium-Catalyzed Double Substitution of 3-Aryl-2-fluoroallyl Acetates with Phenols via C–F Bond Activation - Nomada, Eito; Watanabe, Hirotaka; Yamamoto, Mitsuaki; Udagawa, Takumi; Zhou, Biao; Kobayashi, Akiko; Minakawa, Maki; Kawatsura, Motoi (Synlett, 2014)
The double substitution of 3-aryl-2-fluoroallyl acetates with phenols has been accomplished; the Pd(PPh3)4 catalyst system has effectively catalyzed the reaction to afford the doubly substituted product via carbon–fluorine bond activation.
Keywords: palladium; catalysis; fluorine; phenols; coupling